POTENTIAL ZOONOTIC ENTERIC PARASITES IN ANIMALS IN CAPTIVITY AT THE ZOO IN CALI, COLOMBIA - Fajardo-Sánchez, Jaime Eduardo (2014)
Zoos are places with a high diversity of animals, some of which may have acquired a particular parasite load in both their area of origin or during their captivity. The probability of animal keepers contracting zoonotic diseases increases due to constant contact with the animals in their daily work. This descriptive ecological study was performed in order to establish the presence of intestinal parasites with zoonotic potential in captive animals at the Cali Zoological garden. In february 2013, serial pools of stools from psittacids (3 species), cebids (2 species), atelids (2 species), caviids (1 species), and lemurids (1 species), were collected and analyzed using direct smear and concentration techniques. Convenience sampling taking 53 individuals including mammals and birds was performed, yielding parasitological prevalence of 89%, distributed as follows: 57.2 % for helminths (31.8% Trichurida, 6.35% Ascaridida, 6.35% Uncinarias and 12.7 % Strongyloides sp.) and 31.8% for protozoa (19.05% Entamoeba spp. and 12.70 % Giardia spp.). The presence of potential zoonotic parasites in the positive samples such as Giardia spp., Entamoeba spp. and Strongyloides spp. demands studies in larger populations of animals and species using molecular methods.